The constitutional court's use of human dignity in the interpretation of the South African Bill of Rights: selected cases - Mudarikwa, Mandivavarira (Department of Public Law, 2026)
The Constitutional Court often relies on human dignity in the interpretation of Bill of Rights. Human dignity is a constitutional value enshrined in section 1, section 10, section 36 and section 39 of the Constitution. It is a founding value of the constitution of South Africa. As a foundational value '[i]t reinforces rights claims, gives direction to or informs the extent and scope of other rights and it is emphasised to determine whether violations of such rights have occurred. Human dignity is an inherent attribute of human beings, a characteristic of life which protects people from actions that fail to recognize that everyone is equal in dignity and worth. It is not very clear what the role of human dignity is in the interpretation of the Bill of Rights by the Constitutional Court. It has been linked to equality, transformation of society, right to life, cruel and inhumane punishment, and freedoms. The link to any of these concepts has not been clearly explained by the Court.